Switchable magnetic, dielectric, conductivity, and phase transition properties of charge-transfer crystals - Yu, S. S.; Zhao, H. R.; Xu, W.; Zhang, H.; Duan, H. B. (Frontiers in Electronic Materials, 2022)
The properties can be switch between different states, and can be used in sensors, display and memory devices. In this study, two multi-functional switchable materials [C5-Pmim][Ni(mnt)2] (1) and [C6-Hmim][Ni(mnt)2] (2) (where mnt2- = maleonitriledithiolate, C5-Pmim = 1-pentyl-3-methylimidazolium, C6-Hmim = 1-hexyl-3-methylimidazolium) have been designed and synthesized, which has segregated cations and anions stacks in crystal structure. 1 shows two-step switchable dielectric transition with thermal hysteresis loop accompanying structure phase transition. Dielectric transition of 1 can be attributed to the reorientation of the polar cations and crystal to mesophase transition. Switchable conductivity properties of 1 and 2 were realized by crystal to mesophase structure transition. The conductivity of mesophase for 1 and 2 is higher than corresponding crystal phase. Furthermore, magnetic phase transition with non-common hysteresis loop for 2 is observed triggered by structure and dielectric transition. To the best of our knowledge, this work might be the rare multi-functional switchable examples with dielectric, conductivity and magnetic transition.